AN ANALYSIS OF THE EIGHTH GRADE STUDENTS' WRITING DEFICIENCY AT SMP NEGERI 5 MELAYA IN ACADEMIC YEAR 2016/2017 - ., Ni Kadek Nelly Yuniartini; ., Prof. Dr. Dewa Komang Tantra, M.Sc.; ., Putu Eka Dambayana S., S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed at analyzing (1) the deficiencies which are found in the students’ writing different text genres and (2) the causes of deficiencies found in the students’ writing different text genres of grade VIII Negeri 5 Melaya in academic year 2016/2017. The instrument used for data collection were writing task, rubrics and interview guideline. The methods of data collection were analyzing students’ writing task and interview. The result of the study showed that most of students’ writing descriptive and recount text contained of grammatical and mechanics deficiency. The causes of students’ writing deficiency that were mostly found such as minimum knowledge of how to write a good paragraph, lack of feedback from the teacher, confusion in choosing verb tense and students’ carelessness of punctuation in writing text. Kata Kunci : Descriptive text, Recount Text, and Writing Deficiency. Penelitian ini bertujuan untuk menganalisis (1) kekurangan yang ditemukan pada penulisan teks berbeda genre dan (2) penyebab kekurangan yang ditemukan pada penulisan teks berbeda genre siswa kelas VIII Negeri 5 Melaya pada tahun akademik 2016/2017. Instrumen yang digunakan untuk pengumpulan data adalah penulisan tugas, rubrik dan pedoman wawancara. Metode pengumpulan data menganalisis tugas dan wawancara siswa. Hasil penelitian menunjukkan bahwa sebagian besar tulisan teks deskriptif dan recount siswa mengandung kekurangan gramatikal dan mekanika. Penyebab kekurangan menulis siswa yang banyak ditemukan seperti pengetahuan minimal tentang bagaimana menulis paragraf yang baik, kurangnya umpan balik dari guru, kebingungan dalam memilih kata kerja dan kecerobohan siswa dalam penulisan tanda baca pada teks.keyword : Teks Deskriptif, Teks Recount, dan Kekurangan Penulisan.